PROFIL SWAMEDIKASI OSTEOARTRITIS PADA LANSIA DI APOTEK WILAYAH KABUPATEN KLATEN - Etikasari, Ria; Naza Dewi Maulana; Dina Fakhriya (Nusantara Hasana Journal, 2025)
Self-medication is an effort made by the community to treat and mantain their health independently. This practice is commonly carried out by the elderly, especially those suffering from osteoarthritis, which has a high prevalence in Indonesia. This study aims to determine the profile of osteoarthritis self-medication among the elderly at pharmacies in Klaten Regency, including respondent characteristics, type of drugs used and side effects experienced. This study was descriptive observational with a cross-sectiobnal point time approach. Data collection used a structured quetionnaire that had been tested for validity and reiability. A total of 96 elderly respondents who practiced self-medication for osteoarthiritis at pharmacies in the Klaten Regency was included . Data analysis was performed using univariate frequency distribution to describe the characteristics of the respondents, treatment profile, and drug side effects. Of the 96 patients, most were aged 60-74 years (59.3%), female (64.6%), had an elementary school education (68.8%), and worked as traders (66.6%). The most commonly used drug was sodium diclofenac (55.2%). A total 54.2% of patients reported experiencing side effecrs from the use of osteoarthritis drugs, such as stomach pain. Osteoarthritis self-medication among the elderly in pharmacies in Klaten Regency was dominated by the use of sodium diclofenc, in accordance with recomendation of the American Colledge of Rheumatology as one of the drugs of choice for osteoarthritis pain. However, side effects still occur frequently, so education on the rational use of drugs, especially in the elderly, is needed.